IMPLEMENTASI KEBIJAKAN PEMERINTAH TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL (PPKS) DI PERGURUAN TINGGI - Ema Mutia Fitri; Asih Widi Lestari; Firman Firdausi; Emei Dwi Nanarhati Setiamandani (Pusat Studi GESI - UWP, 2022)
The implementation of the Government's policy on the Prevention and Handling of Sexual Violence in Higher Education is one of the policies that should be implemented in every university as an effort to fulfill the rights and protection of the academic community. A survey of the Ministry of Education and Culture in 2020 found 77% of lecturers stated that sexual violence had occurred on campus and 63% of them did not report cases they knew to the campus. The high phenomenon of sexual violence in the university environment is a challenge for every university bureaucracy which is expected to be able to produce problem solving in the protection of the academic community. This study aims to determine the implementation of the Government's policy on the Prevention and Handling of Sexual Violence the university environment along with the supporting and inhibiting factors. This study uses qualitative research methods with data collection through observation, interviews and documentation. Determination of informants is done by using snowball sampling.The validity of the data using increased persistence and triangulation. Data analysis was carried out through the stages of data collection, data presentation and drawing conclusions. The results showed that the implementation of government policies on PPKS in universities, especially in UNITRI and UIN Malang, had not been going well. Several indicators of socialization that are not optimal and evenly distributed, availability of resources, lack of understanding and non-uniform perspectives are obstacles in the implementation process. Supporting factors include the existence of rules as the basis for the Government's policy on the Prevention and Handling of Sexual Violence in higher education and mutual agreement to ensure a sense of security and comfort in the learning process.